A descriptive study of the type 2 diabetic population with hypertriglyceridemia of more than 2.5 mmol/l at presentation with subsequent analysis of their baseline and follow up variables - Vermooten, Barbara (Department of Medicine, 2024)
Background Type 2 diabetes mellitus and the dyslipidaemia that often accompanies it are major risk factors for atherosclerotic cardiovascular disease. Elevated triglycerides mark the accumulation of atherogenic remnant lipoproteins. Because there is little South African data on hypertriglyceridaemia in diabetes we retrospectively reviewed baseline and follow-up data of patients attending a specialized lipid clinic. Aim of the study The primary aim of this study is to describe biochemical and demographic variations of a diabetic population with hypertriglyceridemia and to further investigate whether there are correlations between glycemic control, lipid modifying therapy and hypoglycemic therapy with lipid outcomes, specifically LDL cholesterol, remnant cholesterol, triglycerides, and HDL-C. Methods We reviewed the medical records of 100 diabetic patients with hypertriglyceridemia of >2.5mmol/L who attended the Groote Schuur Hospital Lipid clinic for at least two years. The patients were randomly selected from the Lipidology database, and selection was made based on inclusion criteria for this study. We documented four six-monthly follow-up visits and documented the visit with the lowest recorded triglyceride levels if it was outside the two-year follow-up. Results The study population was predominantly (63%) female with a mean (SD) age at presentation of 50.87 (10.44) years. Obesity (BMI >30 kg/m²) was highly prevalent (66.3%) and diabetes was generally poorly controlled (76.16% patients had a HbA1C >7%). Baseline triglycerides ranged from 2.6mmol/L to 63.3mmol/L with a median and mean (SD) of 4.64 mmol/L and 10.47 (12.57) mmol/L, respectively. Baseline agarose electrophoresis patterns were: 0% type I, 0% type IIA, 51.4% type IIB, 10.3% type III, 18.7% type IV and 19.6% type V. LDL particle size determined by acrylamide gradient gel electrophoresis was intermediate or small in 61 of 64 (95%%) of patients with visible LDL. At baseline calculated mean (SD) remnant cholesterol (48 patients) was 1.55 (0.24) mmol/L, ranging from 1.1mmol/L to 2mmol/L. Triglycerides and calculated remnant cholesterol were strongly correlated (r2=0.9395, p=0.000). There was no correlation between baseline TG and HDL-C, baseline BMI and baseline waist circumference (waist/hip ratio could have possibly corrected for different anthropometry), but there was a positive correlation between triglycerides and alcohol intake, (r2=0.224, P=0.012). There was no correlation between baseline triglycerides and HbA1C (p=0.8423) or fasting glucose (p=0.0857). The change in total triglycerides from initial presentation to the follow-up visit with the lowest documented value was a mean (SD) decrease of 2.91 (4.98) mmol/L, ranging from either no change to a decrease of 32.68mmol/L. The mean (SD) reduction in HbA1C was 0.94 (1.64) % ranging from an increase of 1.7% to a decrease of 7.8%. Fibrates were initiated in 43% of patients. Patients prescribed fibrates had higher mean (SD) baseline TG levels of 18.56(15.48) mmol/L, compared to levels of 4.11(1.85) mmol/L in patients who were not prescribed a fibrate. At baseline mean (SD) TC values were 8.33 (3.18). The mean (SD) LDLC at baseline was 4.26 (1.45) mmol/L ranging from 0.5 to 7.6 mmol/L. Only 4.1% of all patients with a calculable LDL-C achieved values below 1.8mmol/L during follow-up. Conclusions In this study diabetic patients with elevated triglycerides who attended a specialist lipid clinic were frequently obese and often had poorly controlled diabetes. Although dyslipidaemia and glycaemia improved following intensification of therapy most patients did not reach their treatment goals. Our study highlights the heterogeneity of hypertriglyceridaemia, the difficulties of achieving good metabolic control, and the need for ongoing follow-up as severe hypertriglyceridaemia relapses readily.